Using position data to estimate effects of perceptual features of play on passing decisions in soccer - Steiner, S.; Rauh, S.; Rumo, M.; Sonderegger, K.; Seiler, R. (Current Issues in Sport Science, 2018)
Passes are a performance-relevant parameter in many team sports. They must be played in the highly dynamic and unpredictable contexts of interactive team competitions. The difficulty to plan passes in advance requires real-time decisions and highlights the importance of the perceptual information provided by current game contexts. This study estimates the relevance of perceptual information to passing decisions at an ecological scale by analyzing sports data from real competitions. In support of previous findings of a scenario-based investigation, open passing lanes, spatial proximity to the ball carrier, team members` positions in front of the ball carrier, and loose defense by opposing players all significantly increased team members` odds for receiving passes. Together, the four kinds of perceptual information enabled the correct prediction of 41% of the passes played. The prediction rate compares to a base rate of 11% and is substantially higher than that for passing decisions made in static game scenarios. The results are interpreted with regard to the relevance of the perceptual information to passing decisions made in time-constrained competitive situations.